Assessing physical activity with the wearable cardioverter defibrillator in patients with newly diagnosed heart failure - Iliodromitis, Konstantinos; Balogh, Zsuzsanna; Triposkiadis, Filippos; Deftereos, Spyridon; Vrachatis, Dimitrios; Bimpong-Buta, Nana-Yaw; Schiedat, Fabian; Bogossian, Harilaos (Frontiers in Cardiovascular Medicine, 2023)
Background The wearable cardioverter defibrillator (WCD), (LifeVest, ZOLL, Pittsburgh, PA, USA) is a medical device designed for the temporary detection and treatment of malignant ventricular tachyarrhythmias. WCD telemonitoring features enable the evaluation of the physical activity (PhA) of the patients. We sought to assess with the WCD the PhA of patients with newly diagnosed heart failure. Methods We collected and analyzed the data of all patients treated with the WCD in our clinic. Patients with newly diagnosed ischemic, or non-ischemic cardiomyopathy and severely reduced ejection fraction, who were treated with the WCD for at least 28 consecutive days and had a compliance of at least 18 h the day were included. Results Seventy-seven patients were eligible for analysis. Thirty-seven patients suffered from ischemic and 40 from non-ischemic heart disease. The average days the WCD was carried was 77.3 ± 44.6 days and the mean wearing time was 22.8 ± 2.1 h. The patients showed significantly increased PhA measured by daily steps between the first two and the last two weeks (Mean steps in the first 2 weeks: 4,952.6 ± 3,052.7 vs. mean steps in the last 2 weeks: 6,119.6 ± 3,776.2, p-value: < 0.001). In the end of the surveillance period an increase of the ejection fraction was observed (LVEF-before: 25.8 ± 6.6% vs. LVEF-after: 37.5 ± 10.6%, p < 0.001). Improvement of the EF did not correlate with the improvement of PhA. Conclusion The WCD provides useful information regarding patient PhA and may be additionally utilized for early heart failure treatment adjustment.